Depositionally-Induced Magnetic Frequency Variations of a Sandstone Facies of the Copper Harbor Conglomerate from the North American, Mid-Continent Rift at Union Bay, Michigan - (:unkn) unknown (My University, 2018)
The Mesoproterozoic, Copper Harbor Conglomerate Sandstone Facies of Union Bay, Michigan was investigated to determine whether fluvial red beds from deep time can maintain magnetic variations related to deposition. Additionally, the possibility that magnetic variations represent astronomically forced climate cycles was also explored at this site. The study utilized environmental magnetism and cyclostratigraphic techniques. The magnetic mineralogy was characterized using temperature dependent susceptibility, isothermal remanent magnetization, and anisotropy of magnetic susceptibility to determine composition, approximate grain size, abundance, and magnetic shape and orientation. For a partial cyclostratigraphic study, sequential, outcrop based magnetic susceptibly measurements were taken stratigraphically every 0.47 m on average, over 56.4 m. Fine-grained magnetite and hematite were inferred from laboratory measurements, and the assemblage of magnetic grains were determined to be primarily prolate. The magnetic fabric agreed with previous paleocurrent field observations at the site, with a flow directionality towards the northwest, suggestive that susceptibility correlates with depositional orientation. Hematite concentration was determined to control susceptibility, and fluctuations in its abundance were observed to be related to physical outcrop properties. High susceptibility corresponded with physically larger grain sizes and was associated with cross-bedding, meanwhile low susceptibility was attributed to physically smaller grain sizes as well as erosional and color boundaries. A statistically-significant periodic susceptibility signal was observed approximately every 2 m from the stratigraphy. The cyclicity of the signal suggests that susceptibility variations may arise from climatically-induced variations in depositional or post-depositional processes. Due to the uncertainty in the positioning of this section in absolute time, our study precludes a relationship between the observed periodic signal and astronomically forced climate cycles. However, the ability to isolate a cyclical signal in these deep time, fluvial red beds suggest that Precambrian deposits are potential candidates for full cyclostratigraphic studies provided there are fewer unknowns related to absolute depositional timescales.
Keywords: Copper Harbor Conglomerate; Environmental magnetism